Synthesis, characterization, and photocatalytic properties of core/shell mesoporous silica nanospheres supporting nanocrystalline titania - Cendrowski, Krysztof; Chen, X.; Zielinska, B.; Kalenczuk, R. J.; Rümmeli, M. H.; Büchner, B.; Klingeler, Rüdiger; Borowiak-Palen, E. (Journal of nanoparticle research, 2011)
The facile bulk synthesis of silica nanospheres makes them an attractive support for the transport of chemical compounds such as nanocrystalline titanium dioxide. In this contribution we present a promising route for the synthesis of mesoporous silica nanospheres (m-SiO2) with diameter in range 200 nm, which are ideal supports for nanocrystalline titanium dioxide (TiO2). The detailed microscopic and spectroscopic characterizations of core/shell structure (m-SiO2/TiO2) were conducted. Moreover, the photocatalytic potential of the nanostructures was investigated via phenol decomposition and hydrogen generation. A clear enhancement of photoactivity in both reactions as compared to commercial TiO2-Degussa P25 catalyst is detected.
Gesehen am 28.06.2022